Plankton distribution within a young cyclonic eddy off south-western Madagascar. (August 2019) - Noyon, Margaux; Morris, Tamaryn; Walker, David; Huggett, Jenny
Abstract: Mesoscale eddies are major features in ocean dynamics that significantly influence ocean production depending on their polarity, life-stage, location and time of formation. Eddies in the south-west Indian Ocean have been the focus of many studies, especially in the Mozambique Channel where southward-moving cyclonic and anticyclonic eddies feed into the Agulhas Current. However, eddies formed south of Madagascar that move westwards towards the coast of South Africa have been much less studied, despite their significant contribution to the Agulhas Current. This study aims to understand how the plankton communities (i.e. pico-, nano-, phyto-, microzoo- and mesozooplankton) are distributed in a cyclonic eddy generated off southern Madagascar. We also investigate a possible link between the Madagascar shelf and the eddy. Temperature, salinity, fluorescence and plankton abundance were measured at 25 stations spaced at 18.5 km intervals across a young (~ 1 month old) cyclonic eddy, and at three locations on the Madagascar shelf, in July 2013. A patch of enhanced chlorophyll a concentration was found at four stations in the eddy, homogeneously distributed vertically in the upper mixed layer and characterised by a higher proportion of diatoms compared to the other stations. Abundances of picoplankton, nanoplankton, ciliates and dinoflagellates were very similar within and outside the eddy. Zooplankton followed a contrasting pattern with higher biomass at four stations just to the west of this high diatom patch. The mesozooplankton composition at these four stations revealed greater species similarities with the Madagascar shelf than with the other stations, suggesting a link between the shelf and the western side of the eddy. The periphery of the eddy seems to have been primarily influenced by a strong geostrophic current propagating from the southern shelf of Madagascar which then wrapped itself around the eddy. This filament may be the source of the high zooplankton biomass in the eddy periphery, which would account for the similarities in zooplankton community composition between the eddy periphery and the shelf.